Radon Natural Radioactivity Measurements for Evaluation of Primary Pollutants - Fenjuan Wang; Zhenyi Zhang; Maria Pia Ancora; Xiaodong Deng; Hua Zhang (The Scientific World Journal)
Radon is naturally released from the soil into the surface layer of the atmosphere, and by monitoring the natural radioactivity data of radon and its shot-live decay products we can get valuable information about the dilution properties of the lower boundary layer. This paper explores the dispersion characteristics of the lower layer of the atmosphere in Lanzhou, China, and the close relationship with the patterns of primary pollutants’ concentrations. Measurements were conducted from July 2007 to May 2008 at one station and a fifty-day campaign was carried out at two stations in Lanzhou. The interpretation of radon radioactivity measurement showed that the measured atmospheric stability index (ASI) data at two stations in Lanzhou had statistically significant correlation, and well described the lower atmospheric layer mixing property in the area. The temporal trend of PM10 data was consistent with the temporal trend of ASI, with almost twice as high values in December than it in August. The results show that the ASI allows to highlight the dilution factor playing an important role in determining primary pollution events, and the mixing properties of the lower boundary layer is the key factor determining PM10 concentration in urban areas.